2015
DOI: 10.1111/1365-2435.12428
|View full text |Cite
|
Sign up to set email alerts
|

Crown plasticity enables trees to optimize canopy packing in mixed‐species forests

Abstract: Summary1. It has been suggested that diverse forests utilize canopy space more efficiently than speciespoor ones, as mixing species with complementary architectural and physiological traits allows trees to pack more densely. However, whether positive canopy packing-diversity relationships are a general feature of forests remains unclear. 2. Using crown allometric data collected for 12 939 trees from permanent forest plots across Europe, we test (i) whether diversity promotes canopy packing across forest types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
308
1
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 343 publications
(336 citation statements)
references
References 51 publications
(178 reference statements)
20
308
1
7
Order By: Relevance
“…Most of the structural indices indicate that Scots pine is less variable, plastic, and multi-layered than beech (Table 6, column (4)). The structural differences between the monocultures of pine and beech are consistent with many other studies (Jucker et al, 2015;Kelty, 1992;Pretzsch, 2014). Scots pine represents a light demanding, rather crown-transparent and vertically oriented fast growing species with an early culminating course of growth (early successional species).…”
Section: Additive and Multiplicative Effects Of Mixing On Stand Strucsupporting
confidence: 89%
“…Most of the structural indices indicate that Scots pine is less variable, plastic, and multi-layered than beech (Table 6, column (4)). The structural differences between the monocultures of pine and beech are consistent with many other studies (Jucker et al, 2015;Kelty, 1992;Pretzsch, 2014). Scots pine represents a light demanding, rather crown-transparent and vertically oriented fast growing species with an early culminating course of growth (early successional species).…”
Section: Additive and Multiplicative Effects Of Mixing On Stand Strucsupporting
confidence: 89%
“…Zhang and Chen (2015) demonstrated that diversity is linked with increased biomass due to increasing tree size inequality in a boreal forest. Similarly, Jucker et al (2015) found that canopy packing was strongly associated with species richness in European permanent forest plots. Our results suggest that canopy packing may influence both AGB and CWP and that both NC and MR effects may contribute to EF indirectly by influencing canopy packing.…”
Section: Discussionmentioning
confidence: 87%
“…Due to the fact that the allometric models do not reflect the crown plasticity, estimates of fractional crown cover and related metrics on the stand-level differ remarkably between TLS and allometric models. In mixed-species stands (like the experimental stand) where crown plasticity is pronounced [55,56], TLS is, therefore, clearly the preferable method.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, a tree's CPA is represented by a circle, i.e., the most compact geometric form in two-dimensional space. Recent studies [55,56] have shown that, especially in mixed-species stands, crown plasticity enables trees to optimize canopy packing, to reduce inter-tree competition, and to maximize the utilization of available photoactive radiation. Obviously, the CPA map ( Figure 5) derived from the TLS data represents a much more efficient usage of the growing space than the maps derived from the allometric models.…”
Section: Crown Morphologymentioning
confidence: 99%